Finland's Romani people = E Rhoma and i Finlandia - Djurić, Rajko Übersetzer; Finnland. Sosiaali- ja terveysministeriö (Brochures Ministry of Social Affairs and Health : 1999, 2000)
Zusammenfassung auf Romanes